FUNDAMENTAL ANALYSIS OF THE COMPANY AS THE BASIS FOR DECISION MAKING OF STOCK INVESTMENT IN THE CONSUMER GOODS INDUSTRY OF THE FOOD AND BEVERAGE SUB-SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE: ANALISIS FUNDAMENTAL PERUSAHAAN SEBAGAI DASAR PENGAMBILAN KEPUTUSAN INVESTASI SAHAM PADA INDUSTRI BARANG KONSUMSI SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Steffi Laurencia; Tria Emi Goulisa; Rudy Sugiharto; Lutfi Alhazami (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2021)
This study aims to select stocks that are worth investing in during the Covid-19 pandemic. To reduce the risk of loss for investors, it is necessary to carry out a fundamental analysis of the company because almost all companies experienced a decline in stock prices during the Covid-19 pandemic. This study produces a fair price for a stock and looks at the company's financial performance in generating profits to determine which shares are worthy of being an investment choice during the Covid-19 pandemic. Data collection using purposive sampling technique using seven companies listed on the Stock Exchange in the food and beverage sub-sector consumer goods industry. The method used is descriptive analysis with a quantitative approach. The results showed that 5 out of 7 companies were in an investment-worthy condition, while two companies were not in an investment-worthy condition